Encouraging Community Empowerment and Local Economic Independence in Villages through Sustainable Economic Development Techniques - Nazeri Nazeri; Rahmat Hidayat; Rina El Maza (Westscience Press, 2024)
With an emphasis on local economic independence and community empowerment, this publication examines sustainable economic development tactics in villages. The purpose of this study is to present an integrated and comprehensive picture of sustainable village economic development. The researcher assesses economic development initiatives in several community areas in Indonesia, using qualitative descriptive methods. The findings of the study show that a comprehensive and integrated approach that considers the economic, social, cultural, and environmental demands of the local population is necessary for sustainable economic development in villages. To achieve local economic independence, community empowerment through active community involvement in the formulation and implementation of economic development programs is very important. The author of this article suggests a sustainable economic development plan for villages that is based on the ideas of community empowerment and participation. Harnessing local resources, strengthening organizations and cooperatives, empowering women and youth, developing small and medium-sized enterprises and the agricultural sector, and implementing sustainable environmental management are all parts of this plan. In conclusion, a comprehensive and integrated approach that emphasizes local economic independence and community empowerment can lead to sustainable economic development in villages. The plan can improve the welfare of the village community and encourage sustainable economic growth.